2009
DOI: 10.1007/s11141-010-9176-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of magneto-gravity waves in the ionosphere by analysis of the maximum observable frequencies on oblique-sounding paths

Abstract: The existence of magneto-gravity waves stipulated by the substorm activity can lead to the occurrence of traveling ionospheric disturbances, whose velocity exceeds the sound speed. For detection of magneto-gravity waves, we used experimental data on propagation of decameter radio waves on the midlatitude and subauroral oblique sounding paths Inskip-Rostov-on-Don, Cyprus-Rostovon-Don, Irkutsk-Rostov-on-Don, and Norilsk-Rostov-on-Don in December 2006 and March 2007 under conditions of weak geomagnetic disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A detailed method of MOF purification from the diurnal variation is presented in [11]. As a result, we obtained new values of the frequencies which contain only MOF variations.…”
Section: Data Usedmentioning
confidence: 99%
“…A detailed method of MOF purification from the diurnal variation is presented in [11]. As a result, we obtained new values of the frequencies which contain only MOF variations.…”
Section: Data Usedmentioning
confidence: 99%
“…However, the excitation of MHD waves in the magnetosphere and conducting ionospheric layers may not necessarily be due to the development of global geomagnetic disturbances. For example, Barkhatova et al [2009Barkhatova et al [ , 2015 have identified MS waves generated by the eastward electrojet and largemagnitude earthquakes. In addition, along with geomagnetic disturbances in the ULF range there were synchronous disturbances in the conducting F2 layer.…”
Section: Introductionmentioning
confidence: 99%
“…Some part of this is due to disturbances caused by of acoustic gravity waves, which changes in the electron concentration of ionospheric layers (Hocke et al, 1996;Kirchengast, 1997;Balthazor and Moffett, 1997;Cai et al, 2011;Song et al, 2012) and well known as traveling iono spheric disturbances (TIDs). It is noted (Sorokin and Fedorovich, 1982;Barkhatova et al, 2009;Barkhatov et al, 2012) that passage of magnetogravity type waves disturb ionospheric layers density as well as geomag netic field components. As sources of ionospheric dis turbances including TIDs auroral electrojets are often considered (Hunsucker, 1982;Afraimovich et al, 2000;Zhivet'ev et al, 2005), natural geophysical events (earthquakes and tsunamis) (Pulinets et al, 1998;Liu J.Y., et al, 2000;Liperovsky et al, 1992;Dabas et al, 2007;Hickey et al, 2009;Perrone et al, 2010;Xu et al, 2010;Liu et al, 2011) as well as high energy events of artificial origin-ground and altitude explosions and artificial heating of the ionosphere (Alperovitch et al, 1985a,b,c) ;Nagorskiy, 1985;Chernogor and Frolov, 2013a,b).…”
Section: Introductionmentioning
confidence: 99%